Pengaruh Model Pembelajaran Advance Organizer Berbasis Peta Konsep Terhadap Hasil Belajar Mahasiswa Matematika Pada Mata Kuliah Stuktur Aljabar - Nurdalilah Nur Dalilah (JURNAL MATHEMATIC PAEDAGOGIC, 2019)
The purpose of this study was to determine whether there was an influence of advance organizer learning models on the learning outcomes of mathematics students. This research is a quasi-experimental study with a pretest posttest control group design. The variables in this study consist of two types, namely the independent variable and the dependent variable. In this study, the independent variable is the advance organizer and conventional learning learning model, while the dependent variable in this study is the learning outcomes of mathematics student learning outcomes in the subject of algebraic structure. The population of this study was all the fifth semester mathematics students of UMN Al-Washliyah Medan. The research sample was V-C class (control class) and V-D class (experimental class). The instrument used is a test, then the data is analyzed by t test. Based on data analysis, mathematics student learning outcomes on the subject of algebraic structures by applying advanced organizer learning models to students is higher than the learning outcomes of mathematics students in the algebraic structure courses by applying conventional lear